Tantangan pelabelan manual dalam pengelolaan koleksi buku di Perpustakaan Terpadu Gunung Batu - Zahra Nurhaliza Insani (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
The university library plays a central role in providing academic information resources and requires systematic collection management to ensure optimal utilization by the academic community. Good collection management is characterized by the neat, orderly arrangement of library materials for easy retrieval and use, with book labeling as a crucial element of this order. At the Gunung Batu Integrated Library, some book collections are still managed using a manual labeling system. In this context, the Program Penguatan Profesi Kepustakawanan Non Kependidikan (P3KNK) provides support through internships in the implementation of library collection management activities. The purpose of this article is to discuss the obstacles encountered in manual labeling in book collection management at the Gunung Batu Integrated Library and its relationship to the role of student P3KNK in assisting with library management activities. This article uses a qualitative descriptive approach to systematically describe the phenomenon of the implementation of P3KNK at the Gunung Batu Integrated Library. The results indicate that manual labeling poses several obstacles, including the relatively long time required, inconsistent label writing, and an increased risk of misplacing collections. Through internship activities, students have the opportunity to apply the librarianship knowledge and skills they learned in lectures through direct practice in the field.